Movement patterns of lions (Panthera leo) in an East African conservancy : avoiding conflict - Haglund, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
The conflict between wildlife, particularly predators, and humans is one of the main reasons for the rapid decline of predator populations. In Kenya, lions (Panthera leo) are a major threat to livestock and humans living around the wildlife conservancies. Ol Pejeta, in Laikipia County, is such a conservancy where three wildlife corridors allows the animals to move freely between the conservancy and adjacent areas. Knowledge about when, and why, the lions move in and out of Ol Pejeta could help understanding how to better manage the population and give information to people living in the area of when the risk of lion depredation might be higher. To investigate the activity patterns of the lions in Ol Pejeta, I compared the passages at the corridors with environmental data such as rain period and moon phase. I also looked at how the lions distributed their activity during the day to see at what time they were most active. Finally I compared the number of passages with gender distribution to see if there was a difference between males and females. The results showed that there was no difference in activity between moon phases but a high significance between rain periods where there was a higher activity during the driest period. I also found that the lions were active right after sunset all the way to sunrise with a peak between 19.00 pm to 20.00 pm, and all passages out of the conservancy occurred during nighttime. There was no difference in passages between males and females. Due to these results, I suggest that the reason for the activity outside the conservancy is due to hunting and that the lions might be hunting for different types of prey during different times of the month which could further help farmers in the area, and the monitoring unit at Ol Pejeta, to know when there might be a higher risk for depredation.